2018
DOI: 10.1002/jhet.3276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Some Novel bis Polyfunctional Pyridine, Pyran, and Thiazole Derivatives

Abstract: In continuation of our efforts to find a new class of antimicrobial agents, treatment of N,N′‐(1,4‐phenylene)bis(2‐cyanoacetamide) (1) with formaldehyde and either benzoylacetonitrile or malononitrile to afford pyridine derivatives 5 and 8, respectively. Similarly, treatment of 1 with different types of aldehydes afforded benzylidene derivatives 9–15, followed by the reaction with rmalononitrile dime to give polyfunctional pyridine derivative 18. Moreover, cyanoacetamide 1 was reacted with chalcone, benzyliden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Recently, a sulfurated analogue of thiazolidinone compounds, the 1,3-thiazolidin-2-thione 76 ( Figure 26 ), was found to act as an antibacterial agent equipotent to chloramphenicol ( 60 ) against S aureus , with a MIC value of 3.12 μg/mL, and with a significant activity also against Bacillus thuringiensis , with a MIC value of 6.25 μg/mL. 133 Despite this interesting activity, thiazole derivative 76 did not demonstrate a significant increase in activity with respect to the pyridine analogue previously reported. Conversely, the authors observed a decrease in the activity against the Gram-negative pathogens was.…”
Section: Antibacterial Activity Of Thiazole Derivatives With Unknown mentioning
confidence: 99%
“…Recently, a sulfurated analogue of thiazolidinone compounds, the 1,3-thiazolidin-2-thione 76 ( Figure 26 ), was found to act as an antibacterial agent equipotent to chloramphenicol ( 60 ) against S aureus , with a MIC value of 3.12 μg/mL, and with a significant activity also against Bacillus thuringiensis , with a MIC value of 6.25 μg/mL. 133 Despite this interesting activity, thiazole derivative 76 did not demonstrate a significant increase in activity with respect to the pyridine analogue previously reported. Conversely, the authors observed a decrease in the activity against the Gram-negative pathogens was.…”
Section: Antibacterial Activity Of Thiazole Derivatives With Unknown mentioning
confidence: 99%
“…Pyridine is also an important heterocycle in medicinal chemistry and is associated with several pharmaceutical activities. [ 11–18 ] Figure 1 represents the concept of drug design based on commercially available drugs isoniazid, fezolamine, and dipyrone heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…El‐Sayed and Fadda synthesized bispolyfunctional pyridine, pyran and thiazole derivatives from N , N ′‐(1,4‐phenylene)bis(2‐cyanoacetamide). By agar diffusion method, derivatives were tested for antimicrobial effectiveness against St. aureus , B. thuringiensis , E. coli , P. aeruginosa , F. oxysporum and B. fabae in comparison to Chloramphenicol, Cephalothin and Cycloheximide.…”
Section: Introductionmentioning
confidence: 99%